2018
DOI: 10.14814/phy2.13648
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the multifactorial nature of ARDS - “Two-hit” approach to model murine acute lung injury

Abstract: Severe acute respiratory distress syndrome (ARDS) presents typically with an initializing event, followed by the need for mechanical ventilation. Most animal models of ALI are limited by the fact that they focus on a singular cause of acute lung injury (ALI) and therefore fail to mimic the complex, multifactorial pathobiology of ARDS. To better capture this scenario, we provide a comprehensive characterization of models of ALI combining two injuries: intra tracheal (i.t.) instillation of LPS or hypochloric aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 53 publications
1
32
0
Order By: Relevance
“…Additionally, indirect pulmonary injuries can be explained by the “2-hit hypothesis” which states that an inflammatory response related to extra-pulmonary area stimulus (first hit) is followed by systemic inflammatory response (second hit) that can induce lung injury. Common triggers of indirect lung injury induced by systemic inflammatory response include sepsis, shock, acute pancreatitis, bone fracture, and massive blood transfusion [ 19 , 20 ]. It has been shown that severe systemic inflammatory response resulting from sepsis produces numerous circulating inflammatory mediators.…”
Section: Overview Of Lung Inflammatory Injurymentioning
confidence: 99%
“…Additionally, indirect pulmonary injuries can be explained by the “2-hit hypothesis” which states that an inflammatory response related to extra-pulmonary area stimulus (first hit) is followed by systemic inflammatory response (second hit) that can induce lung injury. Common triggers of indirect lung injury induced by systemic inflammatory response include sepsis, shock, acute pancreatitis, bone fracture, and massive blood transfusion [ 19 , 20 ]. It has been shown that severe systemic inflammatory response resulting from sepsis produces numerous circulating inflammatory mediators.…”
Section: Overview Of Lung Inflammatory Injurymentioning
confidence: 99%
“…Since patients suffering from ARDS often require ventilatory support, VILI is a complication that eventually aggravates ARDS [ 136 , 214 ]. An early study reported the involvement of P2Y receptors in the pathogenesis of VILI [ 204 ].…”
Section: The Role Of P2 Receptors In Lung Diseasementioning
confidence: 99%
“…However, no significant differences in the oxygenation index, APACHE II and SOFA scores were found between the 2 groups ( P > .05). This indicated that higher mechanical power is more likely to cause ventilator-associated lung injury in patients with ARDS, further induce aggravation of biological injury, [13] lead to increased secretion of TGF-β1 and CTGF, and accelerate the progression of lung tissue fibrosis in patients with ARDS. In the present study, a significant difference was also found in the 28-day mortality in patients between the LMP group and the HMP group, which indicated that the level of mechanical power is related to the prognosis of patients and may be related to the severity of ARDS.…”
Section: Discussionmentioning
confidence: 99%